Quality Assessment of Ground Water in Dhamar City, Yemen - Aizari, Hefdallah Al; Lebkiri, Ahamed; Fadli, Mhammde; Albaseer, Saeed S. (International Journal of Environment, 2018)
Chemical and statistical regression analysis on groundwater at five fields (17 sampling wells) located in Dhamar city, the central highlands of Yemen, was carried out. Samples were collected from the ground water supplies (tube wells) during the year 2015. Physical parameters studied include (values between bracket s represents the measured mean values) temperature (T, 25°), total dissolved solids (TDS, 271.47), pH (7.5), and electrical conductivity (EC, 424.18). The chemical parameters investigated include total hardness (TH, 127.45), calcium (Ca2+, 32.89), magnesium (Mg2+, 11.03), bicarbonate (HCO3̶, 143.84), sulphate (SO42-, 143.84), sodium (Na+, 35.11), potassium (K+, 6.28) and Chloride (Cl ̵, 22.69). The results were compared with drinking water quality standards issued by Yemen standards for drinking water. Except for T° and pH, all other measured parameters fall below the minimum permissible limits. The correlation between various physio-chemical parameters of the studied water wells was performed using Principal Component Analysis (PCA) method. The obtained results show that all water samples are potable and can be safely used for both drinking and irrigation purposes. This comes in agreement with the public notion about groundwater of Dhamar Governorate. Sodium Absorption Ratio (SAR) values were calculated and found below 3 except for one drill. The results revealed that systematic calculations of correlation coefficients between water parameters and regression analysis provide a useful means for rapid monitoring of water quality. International Journal of Environment Volume-6, Issue-4, Sep-Nov 2017, page: 56-71